Assessment of ocular surface diseases in systemic autoimmune conditions - Islam, Mohammad Mazaharul; Sanwar Hossian, M.; Saiful Islam, M.; Mahfujullah, Afzal; Rahman, Shish (International Journal of Research in Medical Sciences, 2024)
Background: Ocular surface inflammation causing dry eye disease (DED) develops in numerous systemic inflammatory/autoimmune conditions. This study aimed to assess the association between ocular surface disorders and psychological and physiological situations among systemic autoimmune patients. Methods: This cross-sectional study included 60 autoimmune rheumatic patients (120 eyes) visiting the department of ophthalmology at BSMMU, Dhaka, Bangladesh from January 2023 to December 2023. Patients were 18 to 80 years old. Pearson and spearman’s analysis were conducted to examine the relationship between systematic conditions and ocular surface conditions. P<0.05 was regarded as statistically significant. Results: The analysis considered the age and sex of the participants. In the study, a higher percentage of autoimmune rheumatic patients’ eyes had DED compared to the control group. Autoimmune rheumatic patients also had higher OSDI scores, lower tear secretion, more severe CFS, and conjunctivochalasis. Additionally, they had lower SF-36 scores, higher anxiety, and HAQ-DI scores. Conclusions: Factors such as quality of life, anxiety, depression, and sleep quality are linked to ocular surface conditions, particularly DED symptoms. The management of systemic conditions and psychotherapy should also be considered as part of the treatment for autoimmune rheumatic patients.